2005
DOI: 10.1016/j.jvs.2005.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Arterioarterial prosthetic loop: A new approach for hemodialysis access

Abstract: The AAPL is an unusual but useful and easy-to-perform alternative procedure to create vascular access for hemodialysis. It can provide survival for strictly selected patients in whom conventional vascular access is not possible. The axillary chest AAPL is preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 29 publications
1
55
1
1
Order By: Relevance
“…These differences were compatible with the observations of our study. 8 Present study demonstrated that the AALG graft achieved primary and secondary patency rates at one year of 73.3 % and 86.6% respectively and this is compatible with the secondary patency rate that was over 70% recommended by the National Kidney Foundation. 13 Although the secondary patency rate of 66.7% at three years was lower than that reported in previously published studies, it was still acceptable with regard to the poor vascular conditions and the missing alternatives for vascular access.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These differences were compatible with the observations of our study. 8 Present study demonstrated that the AALG graft achieved primary and secondary patency rates at one year of 73.3 % and 86.6% respectively and this is compatible with the secondary patency rate that was over 70% recommended by the National Kidney Foundation. 13 Although the secondary patency rate of 66.7% at three years was lower than that reported in previously published studies, it was still acceptable with regard to the poor vascular conditions and the missing alternatives for vascular access.…”
Section: Discussionsupporting
confidence: 88%
“…8 In present study, the desired sufficient extracorporeal blood flow was 300 mL/min, and the painful reperfusion was not observed.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…23,24 Likewise, interarterial loops were not used because of their theoretical risks of ischemia and distal embolization. Zanow 25 and Bunger 20 reported this last complication in 5% and 3.2% of patients with an interarterial axillary-axillary loop for hemodialysis, respectively. To the best of our knowledge, the feasibility of arteriovenous brachial-brachial fistulas was not evaluated in chronic hemodialysis patients who had undergone one or more earlier attempts at surgical vascular access.…”
Section: Discussionmentioning
confidence: 98%
“…Von Zanow et al [21] wurde die Variante eines arterio-arteriellen Schleifeninterponates axillär und femoral mit guten Langzeitresultaten (primäre 1-Jahres-Offenheitsrate von 73% und 54% nach 3 Jahren) und geringen Risiken einer distalen Embolisation beschrieben. [8].…”
Section: "Exotische" Shunts Und Alternativverfahrenunclassified